Correction of Mistakes in Students' Writing - Pašková, Hana
Most effective methods of improving students' writing skills. Arguments for and against correcting students' writing mistakes. Mistake correction improves students' writing skills, therefore teachers should give an accurate, systematic and selective feedback to them.